2015
DOI: 10.1503/cjs.016914
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ultrasonography and surgical strategy in hepatic resection: What difference does it make?

Abstract: Background: With modern advancements in preoperative imaging for liver surgery, intraoperative ultrasonography (IOUS) may be perceived as superfluous. Our aim was to determine if IOUS provides new information that changes surgical strategy in hepatic resection. Methods:We retrospectively analyzed 121 consecutive liver resections performed at a single institution. Preoperative computed tomography and/or magnetic resonance imaging determined the initial surgical strategy. The size, location and number of lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However Richy and his colleagues study on IOUS in 2015 reported 17% change in surgical strategy [14]. This may be due to preoperative MRI were not done routinely to all our cases.…”
Section: Discussionmentioning
confidence: 81%
“…However Richy and his colleagues study on IOUS in 2015 reported 17% change in surgical strategy [14]. This may be due to preoperative MRI were not done routinely to all our cases.…”
Section: Discussionmentioning
confidence: 81%
“…IOUS has been considered as an essential adjunct in hepatic resection. This can provide precise information about the location of the liver lesions and their association with vital anatomical structures, thereby helping guide the surgical strategy [12]. The use of the IOUS offers a chance of cure to an increasing proportion of patients who were considered only for palliative care a few years ago [13].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the IOUS offers a chance of cure to an increasing proportion of patients who were considered only for palliative care a few years ago [13]. IOUS directly alters the preoperative surgical plan by approximately 17% [12]. Previous reports have indicated that it would be very beneficial to switch the scanning of the ultrasonic probe from normal to inverse modality, in order to display the usual appearance of the intrahepatic anatomy of a patient with SIT on the screen [3].…”
Section: Discussionmentioning
confidence: 99%
“…Also intraoperative Doppler ultrasound was used to identify the boundaries of pancreatic mass and to determine the transection line of the pancreas, as well as to identify the splenic vessels. 46,47 We herein present the first case of totally robotic distal pancreatectomy, left hemihepatectomy and splenectomy for PNET with no severe perioperative comorbidity and optimal oncologic outcomes. As the tumor was stable and localized in just pancreas and liver, she was offered surgery with both curative and cytoreductive intent.…”
Section: Discussionmentioning
confidence: 99%